Indonesia dalam Pertautan Budaya Pembangunan dan Budaya Warga Desa - Agusta, Ivanovich (Wacana, Journal of the Humanities of Indonesia, 2007)
The construction of the next imagined-village as a part of the next imagined-Indonesia evokes the need of a new genre on embedding the culture of development and the culture of civil-village. The article presents an "Until-Where" genre (on where the aims of development are reached). In the genre, praxis orientation becomes a context of both cultural analysis and social structure. The deconstructive critique of the culture of development is focused on Kantian humanism, evolutionism and development planning, the politics of space, and capitalization on village development. Co-articulation between the culture of development (which has the tendency for uniformity) and the culture of civil-village (which has the tendency for variation) is constructed, firstly, on toleration between the stake-holders for social transformation. Then the article proposes "Praxis of Familiation", i.e. imagination on the family structure as a translation process for external influence. Focused on the lower stratum, the familiation should be used to empower the lowest one.